H9N2 Viruses Isolated From Mammals Replicated in Mice at Higher Levels Than Avian-Origin Viruses - Sun, Haiwei; Wang, Kai; Yao, Wei; Liu, Qinfang; Yang, Jianmei; Teng, Qiaoyang; Li, Xuesong; Li, Zejun; Chen, Hongjun (Frontiers in Microbiology, 2019)
H9N2 subtype influenza A virus (IAV) has more than 20 genotypes that are able to cross species barriers and expand from birds to mammals and humans. To better understand the impact of different H9N2 genotypes and their characteristics, five H9N2 viruses from different hosts including chickens, geese, pigs, mink, and humans representing the B69 88(Gs/14, Ck/15, and Mi/14), B35 (Sw/08) and G9 genotypes (Hu/04) were infected in chicken and mice. In mice, mammal-origin viruses replicated at higher levels in the lungs compared to avian viruses. The goose-virus replicated at the lowest levels indicating poor adaptation. Increased pro-inflammatory cytokines were positively correlated with viral loads in the lung. In chickens, all viruses were excreted from cloacal and/or oropharyngeal swabs. Interestingly, Mink-origin virus exhibited higher virulence and replication in mice and chickens. Our data indicate that mammal-origin H9N2 viruses are more adapted and virulent in mice than the avian-origin viruses.